Size-controlled synthesis of urchin-like reduced graphene oxide microspheres with highly packed density by emulsion-assisted in-situ assembly and their supercapacitor performance. (August 2018) - Yue, Fang; Gao, Guanqing; Li, Fengting; Zheng, Yiqun; Hou, Shifeng
Abstract: We report a facile water-in-oil (W/O) emulsion method to fabricate urchin-like reduced graphene oxide microspheres (UrGOMSs) with tunable sizes and structures. The success of this synthesis relies on the use of polyethyleneimine and ethylenediamine, acted as an emulsifier and weak crosslinker, respectively, to assist the formation of graphene hydrogel in emulsion droplets, followed by thermal treatment to remove the water. The diameter of the UrGOMSs could be controlled in the range of 2.30–4.58 μm by varying the water-oil ratio and thus the size of emulsion droplets. The UrGOMSs show crumpled surface and urchin-like structure with assembly of graphene nanosheets, which can supply large amount of accessible surface area and efficient ion diffusion pathways. The specific surface area of the structures is up to 356.33 m 2  g −1 with high pack density of 1.37 g cm −3 . When used as electrode materials in supercapacitors, the UrGOMSs exhibit high volumetric capacitance of 527.6 F cm −3 at 10 mV s −1 and 452.1 F cm −3 at 0.2 A g −1 . Furthermore, they also exhibit excellent long-term cycling stability. After 5000 cycles, the capacity retention is around 99.43%. These results indicate the feasibility of the novel strategy for designing densely assembled graphene microspheres for supercapacitors. Graphical abstract: Image 1